Pathogenic waterborne free-living amoebae: An update from selected Southeast Asian countries - Majid, M.A.A.; Mahboob, T.; Mong, B.G.J.; Jaturas, N.; Richard, R.L.; Tan, T.C.; Phimphila, A.; Mahaphonh, P.; Aye, K.N.; Aung, W.L.; Chuah, J.; Ziegler, A.D.; et al. (Public Library of Science, 2017)
Data on the distribution of free-living amoebae is still lacking especially in Southeast Asian region. The aquatic environment revealed a high occurrence of free-living amoebae (FLA) due to its suitable condition and availability of food source, which subsequently causes infection to humans. A total of 94 water samples consisted of both treated and untreated from Laos (31), Myanmar (42), and Singapore (21) were investigated for the presence of pathogenic FLA. Each water sample was filtered and cultured onto non-nutrient agar seeded with live suspension of Escherichia coli and incubated at room temperature. Morphological identification was conducted for both trophozoites and cysts via microscopic stains (Giemsa and immunofluorescence). The presence of Naegleria-like structures was the most frequently encountered in both treated and untreated water samples, followed by Acanthamoeba-like and Vermamoeba-like features. To identify the pathogenic isolates, species-specific primer sets were applied for molecular identification of Acanthamoeba, Naegleria, and Vermamoeba. The pathogenic species of Acanthamoeba lenticulata and A. triangularis were detected from untreated water samples, while Vermamoeba vermiformis was found in both treated and untreated water samples. Our results suggested that poor water quality as well as inadequate maintenance and treatment might be the cause of this alarming problem since chlorine disinfection is ineffective in eradicating these amoebas in treated water samples. Regular monitoring and examination of water qualities are necessary in order to control the growth, hence, further preventing the widespread of FLA infections among the public.